Prospective measurement of outcomes and complications of tibial tuberosity advancement using novel mini plates in small breed dogs - Miller, Leah; Maritato, Karl C.; Kennedy, Shawn C. (Frontiers in Veterinary Science, 2023)
Cranial cruciate ligament disease is a common orthopedic disease in canine patients. Tibial osteotomy procedures for the treatment of small breed (<15kg) cranial cruciate ligament disease have previously been limited. Twenty-two client-owned dogs, 26 stifles, with cranial cruciate ligament disease were treated with novel mini tibial tuberosity advancement plates. The most common intra-operative complications included the need for plate-cage overlap in 7 stifles (26.92%) and screw head fracture in one (3.85%). Post-operative complications included tibial tuberosity fracture (3.85%), post-operative medial patella luxation (7.69%), and persistent lameness (7.69%). Of the 26 stifles evaluated in the medium term ( 6-12 months) postoperatively, 92.3% had no lameness, with the remaining 7.7% having Grade 1 lameness. Good to excellent clinical outcome was noted in all 26 stifles that underwent TTA with novel mini plates.